(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article provides an analysis of the description of homonyms. Homonymy and related concepts:homophony, homography, homomorphism, omophraseology, omosyntagmy, homonymous omolexema, omoform omolexema are described in the literature. It is noted that most of these classifications are based on theoretical interpretations of the formation of homonyms.